Studi Literatur Determinan Merger, Acquisition, dan Foreign Direct Investment di Filipina : Literature Study on Determinants of Mergers, Acquisitions, and Foreign Direct Investment in the Philippines - Rizal, Achmad; Dewangga, Lintang Aji Kusuma; Ardiansyah, Chandra Halim; Navyrianto, Antonius Ariel; Anggraini , Yunita (PT Global Digital Sains Tekno, 2025)
Purpose: To identify key variables (regulations, institutions, political conditions, and macroeconomic conditions) that influence M&A and FDI. This will provide a clearer understanding of the mechanisms of the relationship between M&A and FDI and identify remaining research gaps to support policy formulation. Methods: This study employed a literature review, an approach aimed at collecting, evaluating, and synthesizing relevant existing literature on a specific research topic. Findings: Regulations and policies play a significant role. External factors such as bilateral relations (US–Philippines, China–Philippines), infrastructure quality, and the availability of skilled labor have also been shown to influence investment flows. There is a disparity in benefits: some sectors (banking, infrastructure, public utilities) enjoy more positive impacts, while others are still limited by regulatory and market structure issues. Implications: For the government, this study emphasizes the need for consistency in the application of laws and regulations to promote a healthy and attractive market for foreign investors. For local companies, M&A should not be viewed solely as a means of asset expansion. For foreign investors, regulatory and governance conditions must be considered and considered in acquisition strategies. Originality: This study emphasizes non-financial aspects (regulation, political stability, institutional capacity, governance) that are often overlooked in previous quantitative studies.